2013
DOI: 10.1172/jci69154
|View full text |Cite
|
Sign up to set email alerts
|

Nervous glucose sensing regulates postnatal β cell proliferation and glucose homeostasis

Abstract: How glucose sensing by the nervous system impacts the regulation of β cell mass and function during postnatal development and throughout adulthood is incompletely understood. Here, we studied mice with inactivation of glucose transporter 2 (Glut2) in the nervous system (NG2KO mice). These mice displayed normal energy homeostasis but developed late-onset glucose intolerance due to reduced insulin secretion, which was precipitated by high-fat diet feeding. The β cell mass of adult NG2KO mice was reduced compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 59 publications
(82 reference statements)
6
68
1
1
Order By: Relevance
“…This discrepancy could be due to differences in the species used in these experiments. Also, in our experiments, the reduction in GLUT2 expression was limited to ependymal cells and tanycytes, while in the transgenic line, expression was also affected in neurons sensitive to hypoglycemia located in the brainstem (Tarussio et al, 2014) or neurons in the thalamus involved in carbohydrate preference (Labouebe et al, 2016). We also showed that suppression of GLUT2 expression in tanycytes leads to the loss in response to increased icv glucose, supporting a role for indirect control of glucose over the expression of neuropeptides that control hunger and satiety.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This discrepancy could be due to differences in the species used in these experiments. Also, in our experiments, the reduction in GLUT2 expression was limited to ependymal cells and tanycytes, while in the transgenic line, expression was also affected in neurons sensitive to hypoglycemia located in the brainstem (Tarussio et al, 2014) or neurons in the thalamus involved in carbohydrate preference (Labouebe et al, 2016). We also showed that suppression of GLUT2 expression in tanycytes leads to the loss in response to increased icv glucose, supporting a role for indirect control of glucose over the expression of neuropeptides that control hunger and satiety.…”
Section: Discussionmentioning
confidence: 47%
“…In contrast, icv injections of antisense constructs, designed to specifically to silence GLUT2 expression, reduced feeding and body weight gain in rats (Leloup, Orosco, Serradas, Nicolaidis, & Penicaud, 1998). In mice with specific inactivation of GLUT2 in the central and peripheral nervous systems, no differences in body weight were observed, but progressive glucose intolerance developed (Tarussio et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Analysis of mice with genetic inactivation of Glut2 in the nervous system (NG2KO mice), generated by crossing Glut2 flox mice with a strain of nestin-Cre mice that do not show any metabolic or growth abnormalities [67], provided a new view of the role of nervous glucose sensing in autonomic regulation of the endocrine pancreas [68]. Direct recording of nerve activity showed that the firing rate of the parasympathetic nerve was lower in NG2KO mice than in control mice and was not increased by i.p.…”
Section: Nervous Glucose Sensing and The Regulation Of Islet Cell Masmentioning
confidence: 99%
“…Finally, because knocking out Glut2 in the nervous system leads to suppressed regulation of parasympathetic activity by glucose and impaired control of beta cell mass and function [68], it will be important to identify the glucose-sensing neurons that control this autonomic activity. Identification of these glucose sensing cells may lead to alternative ways of improving insulin secretion capacity in diabetic patients.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…), and insulin tolerance tests (5-h fasted mice, 0.3 units/kg insulin i.p.) were performed as described previously (30). IGF2 ELISA was purchased from R&D Systems (Minneapolis, MN).…”
Section: Biochemical Measurements Glucose and Insulin Tolerance Testsmentioning
confidence: 99%